Status of migration and socio-reproductive impacts on migrants and their families left behind in Nepal. (2nd September 2019) - Thapa, Narbada; Paudel, Mohan; Guragain, Arjun Mani; Thapa, Pukar; Puri, Rupendra; Thapa, Puja; Aryal, Krishna Kumar; Paudel, Binita Kumari; Thapa, Rijan; Stray-Pedersen, Babill
ABSTRACT: This study describes the nature of migration and its socio-reproductive impacts in Nepal. This study utilized the household survey data conducted between April to August 2013, and 15 qualitative interviews with migrants or their family members. About 29.9% of households had at least one member migrated. Almost all migrants (98%) were male with a majority (73.1%) being the husbands of women interviewed. Logistic regression showed the higher proportion of migration in the Western (38.1%) and the Far-western (33.1%) regions of Nepal. The study explored that migration resulted in positive improvements such as meeting family aspirations and economy, and negative impacts such as deception by their employers, feeling loneliness due to separation, an experience of conflicting marital relations, and termination of pregnancy and inability to conceive a baby.